The Impact of Low-Cost Carriers on inbound Tourism of Thailand - Po-Lin Lai; Hyunmi Jang; Chenming Xu; Shi Xin (International Journal of Supply Chain Management, 2019)
Outbound tourism primarily concerns air travel due to the limited options for transportation. Many studies related to aviation and tourism have been conducted. However, most studies are in the US and European context, with only a few cases having been studied in Asia. The purpose of this research is to focus on the development of Low-Cost carriers (LCCs) in major Asian nations. Particularly, it aims to study the influence of LCCs on Thailands tourism. To investigate if LCCs contribute to an increase in Thailands tourism demand, multiple regression analysis with key indicators is employed using monthly data from January 2013 to December 2017. The findings reveal that LCCs have a positive impact on Thailands tourism. Furthermore, LCCs are the main factor in Thailands tourism demand. It is necessary to consider the future development of LCCs and whether LCCs can play an important role in the tourism supply chain in the future.